A atenção a si e ao outro na experiência de crianças autistas com os jogos desenvolvidos para a saúde mental - Henrique, Jordanya Reginaldo (Universidade Federal Rural do Semi-Árido, 2019)
This work has been woven from the desire to analyze how children with autistic spectrum disorder update modes of attention to themselves and the forms of interaction in the direct experience in which they play games built for mental health. We will seek to understand the modes of interaction of subjects with ASD who are cared for in mental health environments. The research we develop is qualitative, in the form of intervention research, using the first-person methodology, inspired by Francisco Varela (2011) and Nize Pellanda (2015). The methodological procedures involve the organization with follow-up workshops. games and the analysis of self-narratives, based on listening to the participants. The accompaniment of the inventive cognition movements related to the attentive ways and the self and the other was based on clues of the cartographic method that guided the analysis in the research. The context of the experience involves children who are clients of CAPSi (Child Psychosocial Care Center) located in the city of Mossoró-RN and their families involved in the service. Two autistic children who follow CAPSi and participate in the Mossoró Network Workshop Program and their families participated in the research. and with the children, filming workshops with the children, for later observation of the ways to coordinate interactive processes in the direct making of the researcher and research collaborators with the use of the K-Hunters game and the space adventure game. Workshops are a research tool, enabling the construction of an experience that favors the updating of cognitive processes, subjectivation processes, learning and care along the way and living with subjects with autistic spectrum disorder. Listening to children and their responsible families is a method, a research path in which the researcher set out to learn sensitive listening in which we distinguish ways of doing, knowing and living.
Keywords: Processos da atenção; Transtorno de espectro autista; Interação; Saúde mental; Jogos digitais; Attention processes; Autistic spectrum disorder; Interaction; Mental health; Digital games; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES